2011
DOI: 10.1037/a0022753
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory deficits are associated with unemployment in persons living with HIV infection.

Abstract: Objective To determine whether deficits in prospective memory (i.e., “remembering to remember”) confer an increased risk of unemployment in individuals living with chronic HIV infection. Methods Fifty-nine Unemployed and 49 Employed individuals with HIV infection underwent comprehensive neuropsychological and medical evaluations, including measures of prospective memory. Results The Unemployed participants demonstrated significantly lower performance on time- and event-based prospective memory, which was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 51 publications
4
59
0
2
Order By: Relevance
“…(1,2,9) The Mini-Mental State Examination showed that 28.2% of older people with HIV in our study had cognitive deficit, with significant association with female sex and age 60 to 69 years; however, we found few data in the scientific literature with which to compare this result. (12,13) In the assessment of mental health/humor we found that 24.1% of elderly patients had dysthymia (mild depression); of these, most were men age 60 to 69 years. However, this result was not significant.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(1,2,9) The Mini-Mental State Examination showed that 28.2% of older people with HIV in our study had cognitive deficit, with significant association with female sex and age 60 to 69 years; however, we found few data in the scientific literature with which to compare this result. (12,13) In the assessment of mental health/humor we found that 24.1% of elderly patients had dysthymia (mild depression); of these, most were men age 60 to 69 years. However, this result was not significant.…”
Section: Discussionmentioning
confidence: 96%
“…This result is similar to the adherence found in the literature showing that older people can guarantee significant control of syndrome manifestation and, at the same time, their longevity as HIV-positive individuals. (11)(12)(13) Effectiveness of adherence to antiretroviral therapy shows a borderline reliability of patients in relation to offering treatment as a way to improve quality of life, in addition to the significant relationship between use of antiretroviral therapy and not being affected by an opportunistic disease. (4,8,11) It is believed that despite the viral suppression provided by the antiretroviral therapy, the level of systemic persistent immune activation and inflammation is low.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of its ecological validity, the MIST has been significantly associated with a variety of important everyday functioning outcomes, including declines in instrumental activities of daily living (Woods, Iudicello, et al, 2008; Woods, Weinborn, Velnoweth, Rooney, & Bucks; 2012), financial mismanagement (Pirogovsky, Woods, Filoteo, & Gilbert, 2012), medication non-adherence (Woods, Moran, Carey, et al, 2008b; Woods et al, 2009), unemployment (Woods et al, 2011), and lower health-related quality of life (Doyle et al, 2012). In fact, results from the above studies suggest that the MIST accounts for variance above and beyond other important predictors like general cognitive status, depression, disease severity, and sociodemographics (e.g., Woods et al, 2009). …”
mentioning
confidence: 99%
“…In terms of its neurocognitive correlates, event-based PM deficits in HIV infection are most prevalent among persons with HIV-associated neurocognitive disorders (HAND, i.e., global neurocognitive dysfunction; Zogg et al, 2011) and are related to impairments in retrospective memory, executive functions, and information processing speed (Zogg et al, 2011). Of clinical relevance, event-based PM deficits are independently associated with higher rates of healthcare non-compliance (Zogg et al, 2010), medication non-adherence (Contardo, Black, Beauvais, Dieckhaus, & Rosen, 2009), dependence in instrumental activities of daily living (Woods et al, 2008), and unemployment (Woods et al, 2011) in HIV. As such, there is a need to understand the cognitive mechanisms of event-based PM in HIV in an effort to inform the development of effective interventions to improve PM and thus optimize real-world outcomes for persons living with HIV infection.…”
mentioning
confidence: 99%